MOTOR STRUCTURE AND BASIC MOVEMENT COMPETENCES IN EARLY CHILD DEVELOPMENT - Rado Pišot; Jurij Planinšec (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2010)
Motor development consists of dynamic and continuous development in motor behaviour and is reflected in motor competences (on the locomotive, manipulative and postural level) and motor abilities (coordination, strength, speed, balance, flexibility, precision and endurance). This is a complex process in which a child acquires motor abilities and knowledge in interaction with inherited and environmental factors. A sample of 603 boys and girls, of which 263 were aged five (age deviation +/- 3 days; 18,5 ± 3,1kg body weight; 109,4 ± 4,3 cm body height) and 340 were aged six and a half (age deviation +/- 3 days; 23, 7 ± 4, 3 kg body weight; 121 ± 4,8 cm body height), were involved in this study after written consent was obtained from their parents. The children's motor structure was established through the application of 28 tests that had been verified on the Slovene population and established as adequate for the study of motor abilities in the sample children. The factor analysis was applied to uncover the latent structure of motor space, and PB (Štalec & Momirović) criteria were used to establish the number of significant basic components. The analysis of the motor space structure revealed certain particularities for each age period. In the sample of 5 year old children, the use of PB criterion revealed four latent motor dimensions, in 6.5 year old children, the latent motor space structure was described with four (boys) and five (girls) factors. Despite the existence of gender differences in motor space structure and certain particularities in each age period mostly related to the factors which influence movement coordination, several very similar dimensions were discovered in both sexes.